Single dose versus multiple doses of rituximab for preemptive therapy of Epstein–Barr virus reactivation after hematopoietic cell transplantation. Issue 1 (2nd January 2019) - Jain, Tania; Kosiorek, Heidi E.; Grys, Thomas E.; Kung, Shu Ting; Shah, Vishal S.; Betcher, Jeffrey A.; Slack, James L.; Leis, Jose F.; Khera, Nandita; Noel, Pierre; Palmer, Jeanne M.; Sproat, Lisa Z.
Abstract: Epstein–Barr virus (EBV) reactivation is an unresolved medical issue after allogeneic hematopoietic stem cell transplantation (HSCT). Rituximab treatment is recommended for EBV reactivation after HSCT but the number of doses of rituximab to use is unclear. In this study, risk factors and outcomes of patients who needed 1 dose vs >1 doses of preemptive rituximab to clear EBV viremia were compared. A higher viral load was more likely to be associated with higher doses of rituximab. Patients whose EBV viremia cleared with 1 dose of rituximab were more likely to have a preceding reduction of immunosuppression. Overall survival (OS) in these 2 cohorts was not different (18.7 vs 26.6 months, respectively, p  = .96). Since rituximab can have side effects and is fairly costly, a predictive model to determine the number of rituximab doses using viral load would be a useful and cost-effective manner to utilize rituximab for this indication.